Large spontaneous exchange bias and giant magnetoresistance in Ni50Mn37−xFexIn13(x=2–4) Heusler alloys. (September 2016) - Jing, Chao; Liu, Yang; Zheng, Dong; Wang, Xiaolong; Sun, Junkun; Zhang, Yuanlei; Liu, Changqin; Deng, Dongmei; Feng, Zhenjie; Xu, Kun; Li, Zhe
Abstract: In the present work, we have obtained a large zero-field cooled exchange-bias (spontaneous exchange bias, SEB) in Ni50 Mn35 Fe2 In13 Heusler alloy. The experimental results indicate that the sample with x =2 exhibits super-spin glass (SSG), super-paramagnetic (SPM), super-ferromagnetic (SFM) and antiferromagnetic (AFM) behaviors in the martensite state at low temperature. Contributing to the complex magnetic interactions, a large SEB effect with the value of 1567 Oe was obtained at 5 K. At the same time, a non-monotonic behavior of spontaneous exchange bias field (spontaneous H EB ) was observed with the variation of temperature, which is resulted from the competition between the volume fraction of SFM clusters and the exchange coupling of the SFM–AFM interface. In addition, during martensitic transformation (MT), extraordinary electrical transport properties of Ni50 Mn37− x Fe x In13 ( x =2–4) alloys have been observed under various external magnetic field. The maximal value of the giant magnetoresistance (GMR) reaches about 57% at 135 K under the external magnetic field change of 50 kOe. The effect of field induced reverse martensitic transformation (FIRMT) on the GMR has been also discussed. Highlights: A large zero-field cooled exchange-bias effect was observed in Ni50 Mn35 Fe2 In13 . A non-monotonic behavior of spontaneous H EB appears in Ni50 Mn35 Fe2 In13 . The maximal value of GMR reaches −57% under Δ H =50 kOe in Ni50 Mn33 Fe4 In13 .